COMPETITIVE ADVANTAGE AND MARKET SHARE OF TELECOMMUNICATION INDUSTRY IN KENYA - NUTHU, IRENE WANJIRU (KABARAK UNIVERSITY, 2015)
Firms across all industries continue to face the most disruptive market conditions in decades. Increased competition has only accelerated and the battle for market share is now more aggressive in the telecommunication industry. The objective of the study was to determine how competitive advantage strategies applied by firms in the telecommunication industry in Kenya influences the market share in the industry. Market share is one of the indicators used to measure the performance of a firm, which is determined by the number of subscribers in the network or the percentage of revenue the firm makes in relation to the others in the market. In order to satisfy the objective of the study, a census study was conducted since the number of firms involved is small. Descriptive survey research design was adopted and data collected from three key players in the telecommunication industry in Kenya (Safaricom ltd, Airtel and Orange). Primary data was collected through a structured interview guide while secondary data was collected by use of desk search techniques from published reports and other documents. Content analysis was used to analyze the qualitative data collected. The study established that all the firms were using differentiation, cost leadership and focus strategies. The usage of the strategies resulted to formulation of products, services, policies and procedures which enhance their businesses. The level of investments in technology contributes largely to the firm economies of scale thus bringing down the cost of production. The findings indicate that the extent of technological innovations adopted by Safaricom is superior in the market. The choice of focus strategy adopted by a firm helps immensely in defining its market share. The firms face similar challenges in the implementation of focus strategy. The researcher recommends that the firms should invest in various technologies and create a wide reliable network infrastructure to enable them grow their market share.
FULL TEXT
Keywords: competitive advantage, competitive strategy, market share, telecommunication industry